Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Consider the one dimensional diffusion equation in an infinite medium given by;

$$\alpha^2U_{xx}(x,t)-U_t(x,t)=-F(x,t), \quad -\infty\lt x \lt\infty \quad \mathrm{and} \quad 0\lt t\lt \infty,\\ U(x,0)=f(x), \\ \lim_{x\to \infty}U(x,t)=\mathrm{finite,} \quad\lim_{x\to -\infty}U(x,t)=\mathrm{finite,}$$

where $F(x,t)$ is a source term and $f(x)$ is the initial temperature distribution.

A) Determine the response of the system, using Laplace transform for

$$F(x,t)=\sin(2\pi t) \ \mathrm{and}\ f(x)=0 .$$

B) Determine the response of the system, using Fourier transform for:

$$F(x,t)=0 \ \mathrm{and}\ f(x)=\delta(x), \quad \mathrm{where}\ \delta(x) \ \mathrm{is\ the Dirac\ impulse\ function}. $$

share|cite|improve this question
    
I have solve the problem a bit. I have found a non-homogeneous ODE after taking the Laplace. But, putting the boundry conditions do not give reasonable results. – mud08 Jan 2 '13 at 7:43
    
math.utsa.edu/~gokhman/ftp//courses/notes/heat.pdf might be useful. – doraemonpaul Jan 2 '13 at 8:43

A)

Let $U(x,t)=V(x,t)-\dfrac{\cos2\pi t}{2\pi}$ ,

Then $U_x(x,t)=V_x(x,t)$

$U_{xx}(x,t)=V_{xx}(x,t)$

$U_t(x,t)=V_t(x,t)+\sin2\pi t$

$\therefore\alpha^2V_{xx}(x,t)-V_t(x,t)-\sin2\pi t=-\sin2\pi t$

$\alpha^2V_{xx}(x,t)-V_t(x,t)=0$

Let $V(x,t)=X(x)T(t)$ ,

Then $\alpha^2X''(x)T(t)-X(x)T'(t)=0$

$X(x)T'(t)=\alpha^2X''(x)T(t)$

$\dfrac{T'(t)}{\alpha^2T(t)}=\dfrac{X''(x)}{X(x)}=-s^2$

$\begin{cases}\dfrac{T'(t)}{T(t)}=-\alpha^2s^2\\X''(x)+s^2X(x)=0\end{cases}$

$\begin{cases}T(t)=c_3(s)e^{-\alpha^2ts^2}\\X(x)=\begin{cases}c_1(s)\sin xs+c_2(s)\dfrac{\pi xs}{L}&\text{when}~s\neq0\\c_1x+c_2&\text{when}~s=0\end{cases}\end{cases}$

$\therefore U(x,t)=\int_0^\infty C_1(s)e^{-\alpha^2ts^2}\sin xs~ds+\int_0^\infty C_2(s)e^{-\alpha^2ts^2}\cos xs~ds-\dfrac{\cos2\pi t}{2\pi}$

$U(x,0)=0$ :

$\int_0^\infty C_1(s)\sin xs~ds+\int_0^\infty C_2(s)\cos xs~ds-1=0$

$\int_0^\infty C_2(s)\cos xs~ds=1-\int_0^\infty C_1(s)\sin xs~ds$

$\mathcal{F}_{c,s\to x}\{C_2(s)\}=1-\mathcal{F}_{s,s\to x}\{C_1(s)\}$

$C_2(s)=\delta(s)-\mathcal{F}^{-1}_{c,x\to s}\{\mathcal{F}_{s,s\to x}\{C_1(s)\}\}$

$\therefore U(x,t)=\int_0^\infty C_1(s)e^{-\alpha^2ts^2}\sin xs~ds+\int_0^\infty\delta(s)e^{-\alpha^2ts^2}\cos xs~ds-\int_0^\infty\mathcal{F}^{-1}_{c,x\to s}\{\mathcal{F}_{s,s\to x}\{C_1(s)\}\}e^{-\alpha^2ts^2}\cos xs~ds-\dfrac{\cos2\pi t}{2\pi}=\int_0^\infty C_1(s)e^{-\alpha^2ts^2}\sin xs~ds-\int_0^\infty\mathcal{F}^{-1}_{c,x\to s}\{\mathcal{F}_{s,s\to x}\{C_1(s)\}\}e^{-\alpha^2ts^2}\cos xs~ds-\dfrac{\cos2\pi t}{2\pi}+1$

B)

Let $U(x,t)=X(x)T(t)$ ,

Then $\alpha^2X''(x)T(t)-X(x)T'(t)=0$

$X(x)T'(t)=\alpha^2X''(x)T(t)$

$\dfrac{T'(t)}{\alpha^2T(t)}=\dfrac{X''(x)}{X(x)}=-s^2$

$\begin{cases}\dfrac{T'(t)}{T(t)}=-\alpha^2s^2\\X''(x)+s^2X(x)=0\end{cases}$

$\begin{cases}T(t)=c_3(s)e^{-\alpha^2ts^2}\\X(x)=\begin{cases}c_1(s)\sin xs+c_2(s)\dfrac{\pi xs}{L}&\text{when}~s\neq0\\c_1x+c_2&\text{when}~s=0\end{cases}\end{cases}$

$\therefore U(x,t)=\int_0^\infty C_1(s)e^{-\alpha^2ts^2}\sin xs~ds+\int_0^\infty C_2(s)e^{-\alpha^2ts^2}\cos xs~ds$

$U(x,0)=\delta(x)$ :

$\int_0^\infty C_1(s)\sin xs~ds+\int_0^\infty C_2(s)\cos xs~ds=\delta(x)$

$\int_0^\infty C_2(s)\cos xs~ds=\delta(x)-\int_0^\infty C_1(s)\sin xs~ds$

$\mathcal{F}_{c,s\to x}\{C_2(s)\}=\delta(x)-\mathcal{F}_{s,s\to x}\{C_1(s)\}$

$C_2(s)=\dfrac{1}{\pi}-\mathcal{F}^{-1}_{c,x\to s}\{\mathcal{F}_{s,s\to x}\{C_1(s)\}\}$

$\therefore U(x,t)=\int_0^\infty C_1(s)e^{-\alpha^2ts^2}\sin xs~ds+\dfrac{1}{\pi}\int_0^\infty e^{-\alpha^2ts^2}\cos xs~ds-\int_0^\infty\mathcal{F}^{-1}_{c,x\to s}\{\mathcal{F}_{s,s\to x}\{C_1(s)\}\}e^{-\alpha^2ts^2}\cos xs~ds=\int_0^\infty C_1(s)e^{-\alpha^2ts^2}\sin xs~ds-\int_0^\infty\mathcal{F}^{-1}_{c,x\to s}\{\mathcal{F}_{s,s\to x}\{C_1(s)\}\}e^{-\alpha^2ts^2}\cos xs~ds+\dfrac{e^{-\frac{x^2}{4\alpha^2t}}}{2\alpha\sqrt{\pi t}}$

share|cite|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.